Expression of SH3 and Multiple Ankyrin Repeat Domains Protein 3 in Mouse Retina - Xu, Yue; Wang, Ya’nan; Tong, Guang’an; Li, Lin; Cheng, Juan; Zhang, Lesha; Xu, Qi; Wang, Liecheng; Zhang, Pingping (Frontiers in Cellular Neuroscience, 2022)
Synapse-associated gene mutations of SH3 and multiple ankyrin repeat domains protein 3(SHANK3) may lead to autism spectrum disorder (ASD). In some ASD cases, patients may also have vision disorders. However, the effects of SHANK3 in the retina are barely mentioned in the literature. In this work, we used wild-type mice to systematically map the distribution of SHANK3 expression in entire mouse retinas. Using western blot analysis and immunofluorescence double-labeling, we identified a large number of prominent cells expressing high levels of SHANK3 in the inner retina, in particular the ganglion cell layer and inner nucleus layer. And the inner plexiform layer and outer nucleus layer were also exhibited positive SHANK3 signals. In the inner layer, GABAergic amacrine cells (ACs) labeled by glutamate decarboxylase were co-localized with SHANK3-positive cells. Dopaminergic ACs (labeled by tyrosine hydroxylase) and cholinergic ACs (labeled by choline acetyltransferase) were also found to contain SHANK3-positive signals. Additionally, most GCs (labeled by Brn3a) were also found to be SHANK3-positive. In the outer retina, bipolar cells (labeled by homeobox protein ChX10) and horizontal cells (labeled by calbindin) were SHANK3-positive. In the outer nucleus layers, the somata of blue cones (labeled by S-opsin) were weekly co-labeled with SHANK3.The inner segments of blue cones and the outer segments of red/green cones (labeled by L/M-opsin) were partially co-localized with SHANK3, and the outer segments of rods (labeled by Rho4D2) were partially SHANK3-positive too. Moreover, SHANK3-positive labeling was also observed in Müller cells (labeled by cellular retinaldehyde-binding protein). These wide expression patterns indicate that SHANK3 may play an important role in the visual signaling pathway.